(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2004)
The analysis of investigated exponents has revealed a deeper effect of examination stress on specialized school pupils’ health conditions. Increase of central regulation mechanisms’ activity was revealed in conditions of examination tension loading of sympathetic nervous system. The pupils, who have sympathotonic regulation, have formed a «risk» group and have more changes in integral exponents of heart rhythm regulation.